Translation Techniques and Acceptance Level of Indonesian Traditional Art Culture Articles - Tuhumena, Wilhemina Ascaria; Maruanaya, Rita Fransina; Akihary, Wilma; Warandy, Sundary (Koli Journal : English Language Education, 2021)
This research aimed to identify the translation techniques used in translating Indonesian traditional art terminology from the source language into the target language, it was from Bahasa into English and to assess the translation quality in terms of the acceptability of Indonesian traditional art terminology. The research was conducted using a qualitative descriptive method. The data were analyzed using Spradley’s theory which consisted of domain, taxonomy, and componential analysis. The results showed that there were three groups of traditional art terminology translated in online articles with the title Indonesian Traditional Art Culture, including music, dances and theatre. It was found that from 7 identified terminology, there were only two techniques used in the translation, they were description and borrowing techniques, especially pure borrowing. Furthermore, it was found that there were 4 terminology whose translation was acceptable and 3 terminology data that was less acceptable